Analisis Kualitas Terjemahan Otomatis Subtitle Pada Channel Youtube (Indo4arab Khalid Nahdi) - Riantika Zahara; Zamzam Nurhuda (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2024)
In the current era, translation plays a crucial role in developing knowledge and technology across various fields. The essence of translation is to convey messages, ideas, thoughts, and emotions from the source language to the target language. This research provides benefits from both theoretical and practical perspectives. Theoretically, this research is expected to enhance knowledge and understanding in translation from Arabic to Indonesian. The qualitative research method used in this study involves collecting and analyzing descriptive data in the form of observable words and behaviours. This study successfully interprets natural linguistic phenomena by utilizing listening, note-taking, and observing the transcripts of Khalid Nahdi's YouTube videos. Based on the analysis of 20 automatic subtitles in the YouTube video "Ziyarati li madinati al-‘arabi fi indunisi" on the channel "Indo4Arab Khalid Nahdi," the translations were found to be inaccurate, unacceptable, and moderately readable. Many untranslated words, inappropriate word choices, and incorrect use of Indonesian affixes cause this issue. The conclusion from the analysis of the automatic translation of the YouTube video "Ziyarati li madinati al-‘arabi fi indunisi" on the channel "Indo4Arab Khalid Nahdi" shows inaccuracies, unacceptability, and moderate readability. The translation requires improvements in word choice and the use of affixes.